Integration of Maqāṣid al-Sharī‘ah Values in the Book Al-Arabiyyah Bayna Yadayk: A Step Toward Recontextualizing Arabic Language Education in the Digital Era - Muhimmatul Mukaromah; Muhammad Anwar Bin Ahmad (Institut Agama Islam Negeri Curup, 2026)
In the era of rapid digital transformation, Arabic language education plays a crucial role not only in developing linguistic competence but also in fostering learners’ moral and spiritual character. However, many contemporary teaching materials tend to emphasize technical language skills while giving limited attention to the integration of Islamic values, creating a gap between educational ideals and classroom practices. Despite the growing discourse on value-based education, empirical studies on the integration of Maqasid al-Shariah into Arabic-language textbooks, particularly in digital learning contexts, remain limited. This study aims to analyze the integration of Maqasid al-Shariah values in the Al-Arabiyyah Bayna Yadayk textbook as a contemporary model for teaching Arabic in the digital age. The researchers employed a qualitative, descriptive-analytical method to analyze the book’s content in light of the five higher objectives of Islamic law: the preservation of religion, life, intellect, progeny, and property. This approach used both printed and digital sources, employing triangulation to enhance academic credibility. The findings reveal that the textbook strikes a balance between linguistic and educational dimensions, incorporating Maqasid-based values into its texts and learning activities, thereby linking language learning with moral refinement and intellectual development. It also employs digital media through its official online platform to facilitate access to knowledge and promote autonomous learning. However, the study identifies challenges in the use of modern technology, including limited interactive features and the need to pay for access to self-assessment tools. The significance of these findings lies in presenting a new vision for Arabic language education that harmonizes authenticity with modernity, positioning Maqasid al-Shariah as a framework for developing an integrated digital curriculum that combines linguistic proficiency with moral education, thus contributing to the advancement of Islamic language pedagogy in line with the demands of the digital era without losing its identity.